Palynological pairing of archaeological rock shelter and swamp deposits on the Arnhem Plateau: Holocene ecological changes at Nawarla Gabarnmang and Swamp 7, Northern Territory - Cassandra Rowe; Janelle Stevenson; Bruno David; Jean-Jacques Delannoy; Ulrike Proske (Vegetation History and Archaeobotany, 2026)

A 150,000-year lacustrine record of the Indo-Australian monsoon from northern Australia - Michael I. Bird; Michael Brand; Rainy Comley; Xennephone Hadeen; Zenobia Jacobs; Cassandra Rowe; Frédérik Saltré; Christopher M. Wurster; Costijn Zwart; Corey J.A. Bradshaw (Quaternary Science Reviews, 2025)

Holocene hydroclimate inferred from alkane isotope and pollen records from monsoonal northern Australia - Michael I. Bird; Michael Brand; Rainy Comley; Xennephone Hadeen; Niels C. Munksgaard; Cassandra Rowe; Christopher M. Wurster; Costijn Zwart (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Holocene climate changes in tropical Australasia based on branched tetraether lipid evidence from Girraween Lagoon, northern Australia - Weiwei Sun; Enlou Zhang; Cassandra Rowe; Michael I. Bird (CATENA, 2025)

Comparing pollen and n-alkane carbon isotope records in a tropical lacustrine environment - Xennephone Hadeen; Cassandra Rowe; Michael Brand; Rainy Comley; Sourav Das; Christopher M. Wurster; Costijn Zwart; Michael I. Bird (Quaternary Science Reviews, 2025)

Taxonomic and environmental significance of Poaceae and Cyperaceae phytoliths from the Northern Territory, Australia - Kelsey C. Boyd; Carlos E. Cordova; Haidee R. Cadd; Cassandra Rowe; Tim J. Cohen (Review of Palaeobotany and Palynology, 2024)

Woody plant phytolith morphology and representation in surface sediments across the Northern Territory, Australia - Kelsey C. Boyd; Carlos E. Cordova; Haidee R. Cadd; Cassandra Rowe; Tim J. Cohen (Review of Palaeobotany and Palynology, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Vegetation changes through stadial and interstadial stages of MIS 4 and MIS 3 based on a palynological analysis of the Girraween Lagoon sediments of Darwin, Australia - Cassandra Rowe; Michael Brand; Christopher M. Wurster; Michael I. Bird (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Exploring palaeoecology in the Northern Territory: the Walanjiwurru rockshelter, vegetation dynamics and shifting social landscapes in Marra Country - Cassandra Rowe; Jeremy Ash; Liam M. Brady; Daryl Wesley; Shaun Evans; David Barrett (Vegetation History and Archaeobotany, 2023)
This paper presents a palynological analysis of sediments from Walanjiwurru 1, a rockshelter located in the Country of the Marra Aboriginal people at Limmen National Park in the Northern Territory (Australia). Analysis seeks to test rockshelter sediments as a framework for research in an environmentally difficult location, and to explore how the palaeoecological record may capture the diversity of people-nature relationships over time in the Northern Territory. The Walanjiwurru 1 pollen record provides an approximate 500-year insight into the rockshelter’s surrounding landscape. Two plant communities demonstrate local presence across this time frame—foremost a drier eucalypt woodland, and a wetter fringing Melaleuca dominated habitat, each with an integrated series of monsoonal forest taxa. With only subtle shifts in vegetation, the Marra’s consistent maintenance of relations with their landscape is observable, and this is discussed in relation to the Walanjiwurru 1’s archaeology and regional European settler colonialism. Charcoal recovery from Walanjiwurru 1 is derived from in situ campfires, making it difficult to conclude on the response of plant types and vegetation communities to long-term landscape burning. Future palaeoecological research off-site from the rockshelter has therefore been recommended.

Integrating charcoal morphology and stable carbon isotope analysis to identify non-grass elongate charcoal in tropical savannas - Emma Rehn; Cassandra Rowe; Sean Ulm; Craig Woodward; Atun Zawadzki; Geraldine Jacobsen; Michael I. Bird (Vegetation History and Archaeobotany, 2022)

A Holocene record of savanna vegetation dynamics in southern lowland Papua New Guinea - Cassandra Rowe; Bruno David; Jerome Mialanes; Sean Ulm; Fiona Petchey; Samantha Aird; Ian J. McNiven; Matthew Leavesley; Thomas Richards (Vegetation History and Archaeobotany, 2020)

Self-reported confusion is related to global and regional β-amyloid: data from the Women’s healthy ageing project - Georgia E. McCluskey; Paul Yates; Victor L. Villemagne; Christopher Rowe; Cassandra E. I. Szoeke (Brain Imaging and Behavior, 2018)

High-resolution radiocarbon dating of marine materials in archaeological contexts: radiocarbon marine reservoir variability between Anadara, Gafrarium, Batissa, Polymesoda spp. and Echinoidea at Caution Bay, Southern Coastal Papua New Guinea - Fiona Petchey; Sean Ulm; Bruno David; Ian J. McNiven; Brit Asmussen; Helene Tomkins; Nic Dolby; Ken Aplin; Thomas Richards; Cassandra Rowe; Matthew Leavesley; Herman Mandui (Archaeological and Anthropological Sciences, 2013)